2011
DOI: 10.12659/msm.881329
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of atrial fibrillation following coronary artery bypass surgery

Abstract: SummaryBackgroundNew-onset atrial fibrillation is the most common form of rhythm disturbance following coronary artery bypass grafting surgery (CABG). It is still unclear which factors have a significant impact on its occurrence after this procedure. The aim of this study was to evaluate clinical predictors of postoperative atrial fibrillation (POAF) after myocardial revascularization.Material/MethodsWe performed a retrospective analysis of 322 patients who underwent the first CABG operation without baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
2
18
1
Order By: Relevance
“…Pre-operative co-morbid conditions, such as hypertension, diabetes, hypercholesterolemia and COPD, were also shown in previous studies to be independent predictors of POAF 4547 ; however this association could not be established in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…Pre-operative co-morbid conditions, such as hypertension, diabetes, hypercholesterolemia and COPD, were also shown in previous studies to be independent predictors of POAF 4547 ; however this association could not be established in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…4 On the contrary, our previous study showed that hypertension, diabetes, and obesity were independently associated with POAF onset. 5 However, at that time we did not investigate the influence of the MS on the POAF occurrence after CABG. The present study shows that the MS is not only independently associated with the POAF in patients who underwent CABG surgery but also associated with POAF irrespective of hypertension, diabetes, and obesity which represents a new finding.…”
Section: Discussionmentioning
confidence: 99%
“…1 The metabolic syndrome (MS) represents a cluster of cardiovascular risk factors (hypertension, obesity, diabetes, and dyslipidemia), and each of them could induce POAF. [2][3][4][5] In the past several years, the impact of the MS on POAF occurrence and short-term outcome in the patients who underwent coronary artery bypass grafting (CABG) has been investigated in a few studies. [6][7][8] However, none of these studies did provide follow-up of longer than 30 days after CABG.…”
Section: Introductionmentioning
confidence: 99%
“…Hypokalemia is more often associated with ventricular tachyarrhythmias, and the development of perioperative ventricular arrhythmias. One of the tasks of this study was how to prevent the occurrence of POAF ( 19 ). The most common drug used to treat POAF in our institution is Amiodarone.…”
Section: Discussionmentioning
confidence: 99%